2021
DOI: 10.3390/ijms22063022
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening for CEBPD-Modulating Compounds in THP-1-Derived Reporter Macrophages Identifies Anti-Inflammatory HDAC and BET Inhibitors

Abstract: This study aimed to identify alternative anti-inflammatory compounds that modulate the activity of a relevant transcription factor, CCAAT/enhancer binding protein delta (C/EBPδ). C/EBPδ is a master regulator of inflammatory responses in macrophages (Mϕ) and is mainly regulated at the level of CEBPD gene transcription initiation. To screen for CEBPD-modulating compounds, we generated a THP-1-derived reporter cell line stably expressing secreted alkaline phosphatase (SEAP) under control of the defined CEBPD prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…Notably, these epigenetic drugs also harbor anti-inflammatory characteristics, e.g., I-BET151 hampers the expression of the proinflammatory genes IL-1β and TNFα in rheumatoid arthritis synovial fibroblasts, leading to a decreased ability in recruiting immune cells and their lowered proliferative capacity ( Klein et al, 2016 ). A recent report by Ullmann et al (2021) demonstrated that treatment with the BET inhibitors I-BET151 and Ro 11–1,464 in cultured macrophages not only increases endogenous levels of the tumor suppressor protein CEBPD, but also downregulates key cytokine genes like CCL2 and IL-6, buttressing their anti-inflammatory functions. Furthermore, beyond the realm of drug therapeutics, natural dietary supplements like Vitamins C, D and E can also enact both anti-inflammatory and epigenetic effects ( Saccone et al, 2015 ; Gerecke et al, 2018 ; Zappe et al, 2018 ; Yang et al, 2019 ).…”
Section: Epigenetic and Anti-inflammatory Therapies In Cancermentioning
confidence: 99%
“…Notably, these epigenetic drugs also harbor anti-inflammatory characteristics, e.g., I-BET151 hampers the expression of the proinflammatory genes IL-1β and TNFα in rheumatoid arthritis synovial fibroblasts, leading to a decreased ability in recruiting immune cells and their lowered proliferative capacity ( Klein et al, 2016 ). A recent report by Ullmann et al (2021) demonstrated that treatment with the BET inhibitors I-BET151 and Ro 11–1,464 in cultured macrophages not only increases endogenous levels of the tumor suppressor protein CEBPD, but also downregulates key cytokine genes like CCL2 and IL-6, buttressing their anti-inflammatory functions. Furthermore, beyond the realm of drug therapeutics, natural dietary supplements like Vitamins C, D and E can also enact both anti-inflammatory and epigenetic effects ( Saccone et al, 2015 ; Gerecke et al, 2018 ; Zappe et al, 2018 ; Yang et al, 2019 ).…”
Section: Epigenetic and Anti-inflammatory Therapies In Cancermentioning
confidence: 99%
“…In particular, patients with high C/EBPδ positive macrophage numbers are likely to benefit from combination therapy, but this hypothesis needs to be addressed in preclinical PDAC models before one could pursue to clinical studies. Although no C/EBPδ inhibitor has yet been clinically approved, a recent study showed that two histone deacetylase (HDAC) inhibitors, suberoylanilide hydroxamic acid (SAHA) and trichostatin A (TSA), abolished endogenous C/EBPδ mRNA expression levels in THP-1 macrophages [ 44 ]. Whether these HDAC inhibitors do reduce C/EBPδ levels in tumor associated macrophages and subsequently potentiate gemcitabine efficacy in PDAC remains to be established in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPδ is a member of the C/EBP family of transcription factors that, according to the current paradigm, potentiates cytokine production and modulates macrophage function, thereby enhancing the inflammatory response [ 5 , 22 ]. In the current manuscript, we show, however, that cytokine levels are not consistently reduced in LPS-stimulated C/EBPδ deficient macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current paradigm, C/EBPδ acts as a pro-inflammatory transcription factor enhancing the expression of pro-inflammatory mediators [ 4 , 5 ]. Indeed, C/EBPδ is shown to regulate IL-1β or collagen-induced cyclo-oxygenase-2 (COX-2) expression [ 6 , 7 , 8 ]; to induce toll-like receptor (TLR)-4 expression and subsequent signalling [ 9 ]; to potentiate Fcγ receptor-mediated tumor necrosis factor alpha (TNFα), macrophage inflammatory protein (MIP)-2 and MIP-1α expression [ 10 ]; to mediate IgG immune complex-induced macrophages inflammatory cytokine and chemokine production in macrophages [ 11 , 12 ]; and to enhance lipopolysaccharide (LPS)-induced IL-6, monocyte chemoattractant protein-1 (MCP-1) and endothelin-1 levels [ 13 ].…”
Section: Introductionmentioning
confidence: 99%